2004
DOI: 10.1104/pp.104.042580
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Enzymes Forming Volatile Esters from Strawberry and Banana

Abstract: Volatile esters are flavor components of the majority of fruits. The last step in their biosynthesis is catalyzed by alcohol acyltransferases (AATs), which link alcohols to acyl moieties. Full-length cDNAs putatively encoding AATs were isolated from fruit of wild strawberry (Fragaria vesca) and banana (Musa sapientum) and compared to the previously isolated SAAT gene from the cultivated strawberry (Fragaria 3 ananassa). The potential role of these enzymes in fruit flavor formation was assessed. To this end, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
281
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(298 citation statements)
references
References 49 publications
6
281
1
3
Order By: Relevance
“…After 48 h of storage at 1 ± 1°C, all treatments showed a decrease in total content from that measured at harvest (8.33 µg/kg). The availability of alcohol compounds is thought to be one of the limiting factors for ester production (Beekwilder et al, 2004) and, as suggested by Ke et al (1994), low O 2 and high CO 2 concentrations are responsible for the accumulation of alcohols, which leads to the production of ethyl esters and the reduction in other esters. In our study, the highest total concentration of alcohols (12.49 µg/kg) was observed in fruits wrapped in the biodegradable film under passive MAP (A treatment), due to the combined effect of change in temperature to 18 ± 1°C (96 h) and high CO 2 concentration in the packages, which, moreover, corresponded to the lowest total ester level found.…”
Section: Fruit Volatile Componentsmentioning
confidence: 99%
“…After 48 h of storage at 1 ± 1°C, all treatments showed a decrease in total content from that measured at harvest (8.33 µg/kg). The availability of alcohol compounds is thought to be one of the limiting factors for ester production (Beekwilder et al, 2004) and, as suggested by Ke et al (1994), low O 2 and high CO 2 concentrations are responsible for the accumulation of alcohols, which leads to the production of ethyl esters and the reduction in other esters. In our study, the highest total concentration of alcohols (12.49 µg/kg) was observed in fruits wrapped in the biodegradable film under passive MAP (A treatment), due to the combined effect of change in temperature to 18 ± 1°C (96 h) and high CO 2 concentration in the packages, which, moreover, corresponded to the lowest total ester level found.…”
Section: Fruit Volatile Componentsmentioning
confidence: 99%
“…In ripe apples, alcohols constitute 6 to 16 % of the total volatiles (8), whereas esters represent, depending on the apple variety, from 80 % in Golden Delicious and Golden Reinders (14,45) to 98 % in Starking Delicious (36). Esters can have linear or branched chains, and their concentration depends on the availability of precursors (37,46,47) and on the selectivity and activity of the enzymes involved (48)(49)(50)(51). Butyl acetate, hexyl acetate, 2-methylbutyl acetate and ethyl 2-methyl--butanoate are the most important esters due to their high content and impact on apple aroma of several varieties (6,52).…”
Section: Volatile Aroma Compounds In Applementioning
confidence: 99%
“…Alcohol acyl transferases (AAT) are capable of combining various alcohols and acyl CoAs, resulting in the synthesis of a wide range of esters, thus accounting for the diversity of esters. Numerous AAT genes have been isolated and characterized in fruit and vegetables (Aharoni et al, 2000;Beekwilder et al, 2004;El-Sharkawy et al, 2005). Aliphatic esters contribute to the aroma of nearly all fruits and are emitted by vegetative tissues.…”
Section: Fatty Acid-derived and Other Lipophylic Flavor Compoundsmentioning
confidence: 99%